2017
DOI: 10.1108/imr-03-2015-0057
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistencies in the behavioural effects of consumer ethnocentrism

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. behaviour. This study addresses this gap by investigating the factors underlying variations in consumer ethnocentric behaviour using reported brand purchases. Product category, product cost and visibility, brand and country of origin of purchased products are investigated for their impact on the differences in the behavioural effects of CET. Permanent repository link Design/methodology/approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
56
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(68 citation statements)
references
References 73 publications
8
56
1
3
Order By: Relevance
“…These findings could reflect the unforeseen negative role of lower class on responses to foreign shopping. The present research extends prior findings by identifying how research on CET fails to explain lower‐class consumers’ response to international shopping (Balabanis & Siamagka, 2017). Second, it identifies the role of social class on consumption in an international context.…”
Section: Introductionsupporting
confidence: 74%
“…These findings could reflect the unforeseen negative role of lower class on responses to foreign shopping. The present research extends prior findings by identifying how research on CET fails to explain lower‐class consumers’ response to international shopping (Balabanis & Siamagka, 2017). Second, it identifies the role of social class on consumption in an international context.…”
Section: Introductionsupporting
confidence: 74%
“…However, ethnocentric tendencies are more durable and stable than attitudes (Balabanis & Siamagka, 2017). nevertheless, ethnocentric behavior may not be static, especially in emerging countries.…”
Section: Personality and National Identitymentioning
confidence: 96%
“…Additional research on ethnocentric behavior has been conducted by Balabanis and Siamagka [58], addressing factors that include product availability, domestic brands, perceived need for the product, perceived vulnerability of different products, and level of economic development of the countries of origin of the brands purchased. The results of He and Lu's study [59] showed that consumer ethnocentrism can exist during the evaluation and selection of brands matched to ethnic groups as well as the origin of the product (local vs. imported); the in-group recommended logos were treated more favorably than the out-group recommended logos by the higher ethnocentrism group.…”
Section: Literature Reviewmentioning
confidence: 99%